The Influence of Reading Intensity toward Writing Skills - Ibnu Mas’ud (Register Journal, 2009)
The aims of this research are to find of reading intensity, to examine the student’ writing skills, and to probe the influence of the students’ reading intensity toward the students’ writing skill. By applyingdescriptive quantitative approach and using correlation research, the subject of the study are the third year students of SMP N 1 Grabag, Kab. Magelang, in the academic year of 2008/2009. Meanwhile, the sample of the research are 40 students of two classes that are taken by applying stratified sampling technique. Furthermore, there are two variables that are analyzed. They are students’ reading intensity as independent variable and students’ writing skill as dependents variable. Based on the calculation of the critical r in the level of significant of 5%, the writer found that rxy aritmethical is higher than rxy table. Therefore, there is influence of reading intensity toward writing skill.Keywords: Reading; Intensity; Writing